Visual Narrative Structure. (19th November 2012) - Cohn, Neil
Abstract: Narratives are an integral part of human expression. In the graphic form, they range from cave paintings to Egyptian hieroglyphics, from the Bayeux Tapestry to modern day comic books (Kunzle, 1973 ;McCloud, 1993 ). Yet not much research has addressed the structure and comprehension of narrative images, for example, how do people create meaning out of sequential images? This piece helps fill the gap by presenting a theory of Narrative Grammar. We describe the basic narrative categories and their relationship to a canonical narrative arc, followed by a discussion of complex structures that extend beyond the canonical schema. This demands that the canonical arc be reconsidered as a generative schema whereby any narrative category can be expanded into a node in a tree structure. Narrative "pacing" is interpreted as a reflection of various patterns of this embedding: conjunction, left‐branching trees, center‐embedded constituencies, and others. Following this, diagnostic methods are proposed for testing narrative categories and constituency. Finally, we outline the applicability of this theory beyond sequential images, such as to film and verbal discourse, and compare this theory with previous approaches to narrative and discourse.